The usefulness of ultrasonography for the early diagnosis of polyneuropathy in patients with type II diabetes mellitus - Amrendra Kumar Mahato; Rakesh Nyasur; Suyogya Wagle; Sailendra Kumar Mahato; Dipak Kumar Yadav; Namrata Dev (Asian Journal of Medical Sciences, 2024)
Background: Diabetic neuropathies, affecting over 50% of diabetes patients, present varied forms of polyneuropathy impacting somatic and autonomic nerves. Clinical assessments, laboratory findings, and nerve conduction studies (NCSs) aid in precise diagnosis, while recent technological advances highlight ultrasonography (US) as a promising, cost-effective diagnostic tool. Aims and Objectives: This study aims to assess the efficacy of US in early polyneuropathy diagnosis in type II diabetes, exploring its potential as an alternative to NCS. Materials and Methods: In this prospective observational study, we enrolled 30 adult patients with type II non-controlled diabetes and 30 age-matched controls, comprising 15 controlled diabetic patients and 15 normal individuals. The comprehensive assessments encompassed history-taking for diabetes duration, hypertension, and diabetic complications, along with clinical examinations and investigations involving nerve electrophysiology and US on one upper limb based on patient complaints. Results: Significant increases in the cross-sectional area (CSA) of the median nerve were observed in diabetic peripheral neuropathy groups compared to controls, with a P<0.001. Similarly, at the level behind the medial epicondyle, the ulnar nerve CSA exhibited a significant increase in the diabetic peripheral neuropathy group (11.7 mm2) compared to controls (6.7 mm2) with a P<0.002. In addition, a significant difference in cross-sectional values was found in the median nerve proximal to the carpal tunnel between the two groups (P<0.05). In contrast, no significant differences were observed at other sites. Regarding the relationship between sonography and NCSs, NCSs showed higher sensitivity, but sonography demonstrated comparable specificity in evaluating diabetic peripheral neuropathy. Conclusion: Peripheral nerve US in the upper limb can be a valuable diagnostic tool for identifying and diagnosing diabetic peripheral neuropathy.